2014
DOI: 10.11646/phytotaxa.174.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Hemiboea malipoensis, a new species of Gesneriaceae from southeastern Yunnan, China

Abstract: Hemiboea malipoensis, a new species of Gesneriaceae from southeastern Yunnan, China, is here described and illustrated. Based on morphological and molecular evidence, it was found to be similar to H. magnibracteata and H. cavaleriei var. paucinervis by conspicuous involucre and anthers fused by entire adaxial surfaces, but can be easily distinguished from the latter two species by its manificat spherical involucre, 3.5–4.5 cm in diameter, cymes with 4–10 flowers, corolla larger, 4.5–5.5 cm long, pale yellow-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,189 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Total genomic DNA was extracted using the CTAB method (Doyle and Doyle ). The ITS and trnL‐F were selected for phylogenetic analyses as these two loci are the most frequently used in phylogenetic studies of Hemiboea and other Gesneriaceae (Zhang et al , Huang et al , Lu et al ). The PCR amplifications and sequencing procedures were according to those described in Guo et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total genomic DNA was extracted using the CTAB method (Doyle and Doyle ). The ITS and trnL‐F were selected for phylogenetic analyses as these two loci are the most frequently used in phylogenetic studies of Hemiboea and other Gesneriaceae (Zhang et al , Huang et al , Lu et al ). The PCR amplifications and sequencing procedures were according to those described in Guo et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Since the previous comprehensive taxonomic revision by Li and Wang () in which 23 species and five varieties were recognized, Hemiboea has increased to at least 37 species and five varieties. Apart from the two Metabriggsia Wang () species which were transferred to Hemiboea by Weber et al (), ten species have been newly found in Guangxi, Guizhou and Yunnan in recent years (Xu et al , , Wen et al , , Pan et al , Zhou et al , Zhang et al , Chen et al , Li et al , Wu et al ). Most if not all the newly described species have narrow or site‐endemic distribution and low abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Clarke is a medium-sized genus of Gesneriaceae distributed in central to southern China, northern Vietnam and Southern Japan (Li and Wang 2004). Recently, nine new species and one new variety were found in Guangxi, Guizhou and Yunnan province of China (Li and Liu 2004; Wei 2010; Xu et al 2010, 2012; Huang et al 2011; Wen et al 2011, 2013; Pan et al 2012; Zhou et al 2013; Zhang et al 2014; Li et al 2018; Chen et al 2018). Meanwhile, Weber et al (2011) transferred two species of the Chinese endemic genus Metabriggsia W. T. Wang (1983) to Hemiboea , based on molecular and morphological evidence.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was further corroborated a the molecular phylogeny, which resolved Metabriggsia taxa as nested within Hemiboea (Weber et al 2011). In addition, eight new species and one new variety have been described in recent years (Li and Liu 2004, Wei 2010, Xu et al 2010, Huang et al 2011, Wen et al 2011, Pan et al 2012, Zhou et al 2013, Zhang et al 2014. Thus, to date, a total of 33 species and six varieties have been recognised in the genus, with all except H. roseoalba S. B. Zhou, X. Hong & F. Wen listed in 'The international plant names index' (IPNI;  www.ipni.…”
Section: Introductionmentioning
confidence: 99%